The morphology and mitochondrial DNA barcode of Knipowitschia caucasica (Berg, 1916) (Gobiiformes: Gobiidae) from Karpuzçay, Levantine Sea, the easternmost record of Knipowitschia species in the Mediterranean Sea - Kovačič, Marcelo; Öztürk, Dilruba Seyhan; Innal, Deniz (Zootaxa, 2023)
Knipowitschia is a sand-goby genus historically comprising 17 species. The congeneric Knipowitschia species show discordance between morphology and genetics in two ways: the morphologically similar species that are clearly distinct by genetics and the morphologically and ecologically distinct populations that are similar by genetics. A sample of Knipowitschia individuals has been collected from Karpuzçay Creek on the Levantine Sea coast. It is the easternmost Mediterranean record of any Knipowitschia, and a number of arguments suggest it is native. Among the presently valid Knipowitschia species, the population was identified by both genetics and morphology as K. caucasica. The detailed morphological description and genetics are provided for this population. The morphology of the present sample fits within the highly variable morphology of east Aegean populations presently recognized as K. caucasica, although with the extreme values of the already known morphological and coloration variability.